Audit Office Size, Audit Quality, and Audit Pricing - Choi, Jong-Hag; Kim, Chansog (Francis); Kim, Jeong-Bon; Zang, Yoonseok (Auditing : a journal of practice and theory, 2010)
Using a large sample of U.S. audit client firms over the period 2000–2005, this paper investigates whether and how the size of a local practice office within an audit firm (hereafter, office size) is a significant, engagement-specific factor determining audit quality and audit fees over and beyond audit firm size at the national level and auditor industry leadership at the city or office level. For our empirical tests, audit quality is measured by unsigned abnormal accruals, and the office size is measured in two different ways: one based on the number of audit clients in each office and the other based on a total of audit fees earned by each office. Our results show that the office size has significantly positive relations with both audit quality and audit fees, even after controlling for national-level audit firm size and office-level industry expertise. These positive relations support the view that large local offices provide higher-quality audits compared with small local offices, and that such quality differences are priced in the market for audit services.